1991
DOI: 10.1159/000182141
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Cues for the Onset of Puberty

Abstract: The hypothesis that the timing of puberty is at least in part stimulated by some ‘metabolic signal’ that tells the central control system of the reproductive axis that the body is becoming large enough, and that there are enough metabolic fuel stores, to support reproductive function has received considerable attention over the past several decades. However, direct experimental support for the hypothesis that mild metabolic changes, such as those that occur slowly during development, are actually capable of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Ellison (1997) proposed that environmental conditions affecting energy availability during human female puberty may underlie variation in adult ovarian function. While the role of hormonal priming in male adolescents remains to be fully elucidated, variation in HPT function and pubertal development in association with energy availability has been documented in rodents, nonhuman primates, and humans (Cameron, 1991;Dubey et al, 1986;Jean-Faucher et al, 1982;Kulin, 1996;Kulin et al, 1982Kulin et al, , 1984. Kulin et al (1984) reported that undernourished Kenyan male adolescents exhibited delayed pubertal LH and FSH increases compared to well-fed controls living in affluent neighborhoods of Nairobi.…”
Section: Reproductive Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…Ellison (1997) proposed that environmental conditions affecting energy availability during human female puberty may underlie variation in adult ovarian function. While the role of hormonal priming in male adolescents remains to be fully elucidated, variation in HPT function and pubertal development in association with energy availability has been documented in rodents, nonhuman primates, and humans (Cameron, 1991;Dubey et al, 1986;Jean-Faucher et al, 1982;Kulin, 1996;Kulin et al, 1982Kulin et al, , 1984. Kulin et al (1984) reported that undernourished Kenyan male adolescents exhibited delayed pubertal LH and FSH increases compared to well-fed controls living in affluent neighborhoods of Nairobi.…”
Section: Reproductive Endocrinologymentioning
confidence: 99%
“…The site of suppression appeared to be the hypothalamus, since bolus injections of GnRH resulted in higher LH and testosterone responses in glucose-supplemented individuals compared to fasting men (Röjdmark, 1987a,b). Forty-eight-hour fasts have also been reported to alter testosterone produc-tion by decreasing LH pulse frequency (Cameron et al, 1991) as well as decreasing LH pulse amplitudes (Veldhuis et al, 1993).…”
Section: Caloric Deficienciesmentioning
confidence: 99%
“…Reproduction in nonprimate mammals and in primates is highly responsive to metabolic alterations (Cameron 1991, Wade & Jones 2004. Deficiencies of metabolic fuels prevent the proper release of gonadotropin releasing hormone (GnRH) from the hypothalamus, thus causing reproductive quiescence (Bergendahl et al 1991, Wahab et al 2013a.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiencies of metabolic fuels prevent the proper release of gonadotropin releasing hormone (GnRH) from the hypothalamus, thus causing reproductive quiescence (Bergendahl et al 1991, Wahab et al 2013a. Initiation of reproductive function is delayed by conditions of negative energy balance while, in adults, merely skipping one daily meal can lead to reproductive quiescence in nonhuman primates (Kennedy & Mitra 1963a, Foster & Olster 1985, Cameron 1991, 1996. Food resumption regularizes the dysfunctional reproductive axis and normalizes reproduction (Parfitt et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Kinder and coworkers (12) have suggested that feed restriction alters ovarian function through a decrease in pulsatile release of UI. Metabolic signal( s) through which chronic feed restriction alters LH and ovarian function have not been elucidated (15,16,17,18).…”
Section: Introductionmentioning
confidence: 99%